CHALLENGES AND STRATEGIES IN NUTRITIONAL ASSISTANCE FOR CHILDREN WITH AUTISM SPECTRUM DISORDER: EXPERIENCE REPORT (REMUNOM, 2024)
The promotion of health for children with Autism Spectrum Disorder through nutrition is a complex challenge faced by families and healthcare professionals. This descriptive study provides insight into the obstacles encountered when developing strategies to deal with the eating behaviors of individuals with Autism Spectrum Disorder. The case report presents an 8-year-old male patient diagnosed with Autism Spectrum Disorder, level 1 support. Features food selectivity often associated with nutrient deficiencies and reduced fiber intake, leading to issues such as constipation and imbalance in intestinal microbiota. This underscores the complexity of the approach needed to promote healthy and adequate eating habits. The involvement of a multidisciplinary team and personalized strategies are necessary to overcome the specific challenges associated with nutrition in this context.